Influência do ambiente agrícola vizinho na comunidade de ácaros plantícolas em fragmentos florestais - Demite, P. R. [UNESP]; Feres, R. J.F. [UNESP]; Lofego, A. C. [UNESP] (FapUNIFESP (SciELO), 2015)
The mite community has been surveyed in Seasonal Semideciduous Forest with three types of surrounding agricultural environments to test the hypothesis that abundance and richness of mites in forest fragments are influenced by the type of agricultural environment. The survey has been carried out in six fragments, divided into sets of two fragments, each one neighboring one sort of agricultural environment: sugarcane crop (FS), orange crop (FO) and pasture (FP). In each fragment, ten individuals of Actinostemon communis (Euphorbiaceae) were selected, five at the edge and five within each fragment. Iphiseiodes zuluagai, often registered in orange crops, was more abundant in the fragments neighboring such crop, as well as some species of Tarsonemidae. In this study, the Phytoseiidae were more abundant in the fragments neighboring pasture, while sugarcane crops probably favored occurrence of phytophagous mites in the neighboring fragments. Tetranychidae were less abundant in FO, which can be explained by periodical use of pesticides in the orange crops. Forest fragments are important for colonies of predators in the neighboring crops, mainly for annual crops such as sugarcane, where the close perennial environment is very important for colonization of the crop. Maintenance of those areas, besides favoring preservation of wild species of mite, is very important to increase diversity of the neighboring agricultural ecosystems.
Influence of agricultural environment on the plant mite community in forest fragments
Keywords: Agroecosystems; Edge effect; Forest fragments; Native areas